The impact of gun violence restraining order laws in the U.S. and firearm suicide among older adults: a longitudinal state-level analysis, 2012-2016 - Altaf Saadi; Kristen R. Choi; Sae Takada; Fred J. Zimmerman (BMC, 2020)
Abstract Background Older adults complete suicide at a disproportionately higher rate compared to the general population, with firearms the most common means of suicide. State gun laws may be a policy remedy. Less is known about Gun Violence Restricting Order (GVRO) laws, which allow for removal of firearms from people deemed to be a danger to themselves or others, and their effects on suicide rates among older adults. The purpose of this study was to examine the association of state firearm laws with the incidence of firearm, non-firearm-related, and total suicide among older adults, with a focus on GVRO laws. Methods This is a longitudinal study of US states using data from 2012 to 2016. The outcome variables were firearm, non-firearm and total suicide rates among older adults. Predictor variables were [1] total number of gun laws to assess for impact of overall firearm legislation at the state level, and [2] GVRO laws. Results The total number of firearm laws, as well as GVRO laws, were negatively associated with firearm-related suicide rate among older adults ages 55-64 and > 65 years-old (p < 0.001). There was a small but significant positive association of total number of firearm laws to non-firearm-related suicide rates and a negative association with total suicide rate. GVRO laws were not significantly associated with non-firearm-related suicide and were negatively associated with total suicide rate. Conclusion Stricter firearm legislation, as well as GVRO laws, are protective against firearm-relate suicides among older adults.